Evaluacion de variedades de maiz y millo en el arreglo yuca intercalada maiz intercalado millo (yuca//maiz//millo) - Contreras A., A. (International Center for Tropical Agriculture, 1990)
In the municipalities of Sabanalarga, Baranca, and Luruaco (Atlantico, Colombia), 4 intercropping trials were established using cassava var. Venezolana, millet var. Cuarentano, and improved maize var. ICA V 106 and ICA V 109 to determine the suitability of this type of cropping system for a region where the highest crop losses are due to summer droughts. Farmers in the area intercrop cassava var. Venezolana with local maize var. Cuba; no specific agronomic recommendations are known. Yields of cassava decreased when intercropped with maize and decreased even more when also intercropped with millet. Av. yields of sole cropped cassava were 14.26 t/ha. No differences were observed among maize var. ICA V 106, ICA V 109, and Cuba. Max. competition with cassava was observed in cassava//millet; local millet var. Cuarentano yielded highest (1.90 t/ha) in this cropping arrangement, followed by 1.6 t/ha in cassava//maize var. V 106//millet. This latter arrangement also gave the highest net returns, whereas the lowest net returns were obtained with cassava//millet. Statistical differences were observed among sites as well as in cassava and millet yields. Plans include further trials on planting distances for all 3 species; multi-site trials in the region are recommended to include this cropping system in the technological package being developed. (AS- CIAT)